2015
DOI: 10.1155/2015/683109
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Polymeric Additives Based on Vinyl Acetate Copolymers as Wax Dispersant and Its Relevance to Polymer Crystallization Mechanisms

Abstract: The present work has main target to study the effect of additives molecular weight and composition on the flow characteristics of wax crude oil at low temperature below pour point temperature. In this respect, maleic anhydride ester-co-vinyl acetate copolymers with varied monomers feed ratios and different alkyl ester lengths, namely, dodecyl, stearyl, and behenyl alkyl chains, were prepared. These polymeric materials were characterized by FTIR,1HNMR, and GPC. The performance of these additives as pour point d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…12 Thus, paraffin wax can be emulsified to form an emulsion system by surfactants, significantly reducing fluid viscosity, which is conducive to pipeline transportation. 13 Moreover, surfactants can reduce the adsorption of paraffin wax by converting the wettability of pipeline walls from oilwetting to water-wetting, 14 promoting paraffin wax removal. Although the paraffin wax is effectively removed by surfactants, the separation of emulsified paraffin wax is difficult, generating emulsified wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Thus, paraffin wax can be emulsified to form an emulsion system by surfactants, significantly reducing fluid viscosity, which is conducive to pipeline transportation. 13 Moreover, surfactants can reduce the adsorption of paraffin wax by converting the wettability of pipeline walls from oilwetting to water-wetting, 14 promoting paraffin wax removal. Although the paraffin wax is effectively removed by surfactants, the separation of emulsified paraffin wax is difficult, generating emulsified wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As the ambient temperature is further decreased, the point in which these crystals become visible is named cloud point (CP). In contrast, the cold filter plugging point (CFPP) may be described as the lowest temperature in which 20 mL of the fuel is able to pass through a 45 μm filter (mesh size) in 60 s under vacuum pressure (0.02 atm). , …”
Section: Introductionmentioning
confidence: 99%
“…The temperature in which the flow stops is named pour point (PP). Should this happen, biodiesel becomes too thick to be pumped from the fuel tank to the engine and may clog filters. , Thus, problems may arise when biodiesel is exposed to winter temperatures during storage as well as during engine use. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many reports have suggested that acrylates with long alkyl side chains show a good dispersant effect [6,7]. Copolymers of acrylate monomers with long alkyl side chains and other monomers have also been reported to produce good results [8,9].…”
Section: Introductionmentioning
confidence: 99%